Antimicrobial Activity of Ayurvedic Hand Sanitizers - Vyas, Palak (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTHand hygiene is the best tool in preventing opportunistic infections caused by different micro organisms and to achieve this, the use of hand sanitizers becomes must in current scenario. The purpose of present study was to prepare an Ayurvedic hand sanitizers incorporating Panchavalkala, the known herbal combination with multi dimensional activities and to evaluate their respective antimicrobial activities. The results were insignificant with antiseptic liquid, but Gel hand wash showed encouraging results in culture sensitivity.